A Monte Carlo simulation and effective thermal conductivity calculation for unidirectional fiber reinforced CMC. (5th February 2016) - Yan, Dongfang; Wen, Jie; Xu, Guoqiang
Highlights: The random distribution of fibers and pores is simulated by Monte Carlo method. The effective thermal conductivity is calculated and the results are presented in statistical forms. The numerical procedure is programmed by APDL codes and executed automatically. Graphical Abstract: Abstract: Due to the high thermal-mechanical performance, ceramic matrix composite (CMC) is regarded as an alternate material for high temperature components of aircrafts. The thermal conductivity of unidirectional CMC is sensitive to its microstructural characteristics. Herein, the Monte Carlo method is introduced to simulate the real distribution of fibers and air pores. The complete procedure is programmed by ANSYS Parametric Design Language and executed automatically. The effective thermal conductivity of this composite at room temperature is calculated. The effect of fiber arrangement as well as matrix porosity with different fiber fractions is studied. The statistic results are gotten and both longitudinal and transverse thermal conductivity are computed. The random arrangement of fibers can result in a deviation of transverse thermal conductivity in different calculation times. The amount of air pores in matrix can also affect thermal conductivity of this material. This method is proved to be valid and accurate by comparison of numeric and experimental data; the relative error is less than 2%. The method can be used as an effective supplement of theoretical analysis and general FEM calculation for thermal conductivity.